Defeated by the nines: nine extracellular strategies to avoid microbe-associated molecular patterns recognition in plants. Issue 7 (19th April 2021) - Buscaill, Pierre; van der Hoorn, Renier A. L.
Abstract : This review discusses and illustrates nine extracellular strategies that plant pathogens and symbionts use to avoid the recognition by cell surface receptors. Abstract: Recognition of microbe-associated molecular patterns (MAMPs) by cell-surface receptors is pivotal in host-microbe interactions. Both pathogens and symbionts establish plant-microbe interactions using fascinating intricate extracellular strategies to avoid recognition. Here we distinguish nine different extracellular strategies to avoid recognition by the host, acting at three different levels. To avoid the accumulation of MAMP precursors (Level 1), microbes take advantage of polymorphisms in both MAMP proteins and glycans, or downregulate MAMP production. To reduce hydrolytic MAMP release (Level 2), microbes shield MAMP precursors with proteins or glycans and inhibit or degrade host-derived hydrolases. And to prevent MAMP perception directly (Level 3), microbes degrade or sequester MAMPs before they are perceived. We discuss examples of these nine strategies and envisage three additional extracellular strategies to avoid MAMP perception in plants.